Comparison of Strengths Between Acrylic Resin Prosthetics with Thermoplastic Acrylic Against Charpy Impact on Artificial Dental Manufacturing - Sri Wahyuni; Sri Murwaningsih (Sociometry Journal of Social Science, Art and Humanity, 2022)
Heat-cured acrylic resin is the most widely used base material to manufacture removable dentures. Because it has aesthetic advantages, is non-toxic, does not irritate the oral mucosa, is inexpensive, and is easy to manipulate and repair. However, this material has drawbacks. Namely, it has microporosity to absorb liquid, and it is easy to fracture if hit on a hard surface or under prolonged use. This study aimed to determine the difference in impact strength between heat-cured acrylic and thermoplastic acrylic against Charpy impact (impact pressure). It can be used as the basis for adding wire or metal plates to increase the material's mechanical strength. This type of research is an experimental laboratory experiment to determine specific treatments' effects. The research samples were heat cured acrylic and thermoplastic acrylic plates with a size of 65 mm x 10 mm x 2.5 mm according to ADA specification no. 12, totaling 16 pieces for each group. The sample criteria are in the form of blocks according to the size, which is smooth and shiny. Data analysis used the One Way Anova and Least Significant Difference test to see the impact strength of heat cured acrylic plate compared to the thermoplastic acrylic plate with a significance level (p=0.05). One Way Anova test results obtained p< 0.05, proving a significant difference between the Heat Cured Acrylic Resin group and the Acrylic Thermoplastic group. The Least Significant Difference calculation results show that the average difference between Heat Cured Acrylic Resin and Thermoplastic Acrylic is 56.8. It is greater than the LSD calculation of 9.802465, which means there is a significant difference between the average Heat Cured Acrylic Resin and Thermoplastic Acrylic. In conclusion, Heat Cured Acrylic Resin plate has a lower impact strength than Thermoplastic Acrylic.